Aesthetic correction of short nail deformity in congenital brachydactyly Type D by distraction lengthening. (November 2022) - Jiang, Yongkang; Hou, Zhidian; Huang, Lei; A. Chi, Jialun; Zhang, Yingfan; Sun, Wenhai
Brachydactyly Type D is a congenital condition of the thumb in which there is a short and broad thumbnail. Although the thumb function is often unaffected, some patients seek surgery for cosmetic improvement. This study aimed to describe our method of distraction lengthening to correct nail deformity in brachydactyly Type D. A total of 163 thumbs in 95 patients underwent this surgery between 2018 and 2021.The mean thumbnail length improved from 9 mm to 15 mm, with a mean percentage increase of 62%. The ratio of nail length to width changed from 0.6 to 1.1, which was equal to normal. The mean increased fingernail length/width ratio was 0.5, with a percentage change of 78%. No obvious surgical scar was observed. The thumb function was not significantly affected. We conclude that aesthetic correction of short nail deformity in brachydactyly Type D can be achieved by distraction lengthening with high satisfaction and without functional impairment. Level of evidence: IV